Aminal linked inorganic–organic hybrid nanoporous materials (HNMs) for CO2 capture and H2 storage applications. Issue 21 (9th February 2016) - Muhammad, Raeesh; Rekha, Pawan; Mohanty, Paritosh
Abstract : Cyclophosphazene based nitrogen-rich aminal-linked inorganic–organic hybrid nanoporous materials were synthesized by a Schiff-base condensation reaction, which captures 18.9 wt% of CO2 . Abstract : Nitrogen-rich aminal linked inorganic–organic hybrid nanoporous materials (HNMs) with cyclophosphazene moieties in the frameworks were synthesized by a Schiff base condensation reaction. The ultra-microporous materials have a specific surface area ( S BET ) upto 976 m 2 g −1 and could capture 18.9 wt% CO2 and 1.6 wt% H2 at 273 and 77 K, respectively, at 1 bar. The materials have a nitrogen content upto 42% which is the highest among the nanoporous materials category. The high nitrogen content is beneficial for several applications such as CO2 capture.